Pulmonary Drug Delivery: A Role for Polymeric Nanoparticles? - d'Angelo, Ivana; Conte, Claudia; Miro, Agnese; Quaglia, Fabiana; Ungaro, Francesca (Current Topics in Medicinal Chemistry, 2015)
Pulmonary drug delivery represents the best way of treating lung diseases, since it allows direct delivery of the drug to the site of action, with few systemic effects. Meanwhile, the lungs may be used as a portal of entry to the body, allowing systemic delivery of drugs via the airway surfaces into the bloodstream. In both cases, the therapeutic effect of the inhaled drug can be optimized by embedding it in appropriately engineered inhalable carriers, which can protect the drug against lung defense mechanisms and promote drug transport across the extracellular and cellular barriers. To this purpose, the attention has been very recently focused on polymeric nanoparticles (NPs). The aim of this review is to offer an overview on the recent advances in NPs for pulmonary drug delivery. After a description of the main challenges encountered in developing novel inhaled products, the design rules to engineer polymeric NPs for inhalation, and in so doing to overcome barriers imposed by the lungs anatomy and physiology, are described. Then, the state-of-art on inhalable biocompatible polymeric NPs based on enzymaticallydegradable natural polymers and biodegradable poly(ester)s is presented, with a special focus on NP-based dry powders for inhalation. Finally, the in vitro/in vivo models useful to address the never-ending toxicological debate related to the use of NPs for inhalation are described.
Keywords: Pulmonary delivery